High Prevalence of inhA Promoter Mutations among Patients with Drug-Resistant Tuberculosis in KwaZulu-Natal, South Africa - Niehaus, Abraham J.; Mlisana, Koleka; Gandhi, Neel R.; Mathema, Barun; Brust, James C. M. (PloS one, 2015)
Drug-resistant tuberculosis (TB) remains extremely difficult to treat because there are often few remaining active medications and limited diagnostic options to detect resistance. Resistance to isoniazid is typically caused by mutations in either katG or the inhA promoter. inhA mutations confer low-level resistance to isoniazid and cross-resistance to ethionamide while katG mutations confer high-level isoniazid resistance and no cross-resistance. Line Probe Assays (LPAs) that detect mutations in katG and inhA are currently performed on all positive TB cultures in KwaZulu-Natal province, South Africa, but the frequency of inhA mutations in drug-resistant TB patients has not been examined. We sought to determine the proportion of patients who could potentially benefit from high-dose isoniazid and who may be resistant to ethionamide. We reviewed 994 LPA (Hain MTBDRplus) results at the TB reference laboratory in KwaZulu-Natal to determine the frequency of mutations in either katG or the inhA promoter. We stratified these results by drug-resistance category (i.e., MDR-TB, pre-XDR-TB, and XDR-TB) as determined by phenotypic drug-susceptibility testing. Among MDR- and XDR-TB isolates, the prevalence of inhA mutations without a concurrent katG mutation was 14.8% and 10.3% respectively. The prevalence of inhA mutations with OR without a katG mutation was 30.3% and 82.8%, respectively. More than 10% of patients with MDR- and XDR-TB may benefit from high-dose isoniazid. Although ethionamide is empirically included in all MDR- and XDR-TB regimens, nearly a third of MDR-TB patients and a majority of XDR-TB patients likely have resistance to ethionamide. Laboratories performing line probe assays should report specific band patterns so that clinicians may adjust treatment regimens accordingly.